Endothelial damage and cardiac dysfunction in the pathophysiology of severe dengue in adults - Chia, Po Ying (Nanyang Technological University, 2023)
Dengue infection is the most abundant arbovirus infection globally, affecting more than half the world’s population and is predicted to increase with climate change. Disease caused by the dengue virus ranges from asymptomatic to life threatening disease, and the main pathogenesis of severe dengue is increased vascular permeability resulting in shock and end-organ damage. Despite the global burden of disease, there is no specific treatment for dengue infection and only supportive care is available. There are also no biomarkers available to predict the severity of disease in early dengue illness. In this thesis, I present the results of a prospective observational study of dengue participants investigating the pathogenesis of dengue shock and potential upstream host mediators. Both vascular hyperpermeability and cardiac dysfunction were evaluated, along with potential neutrophil and mast cell mediators. The results of the study are then used to identify targets for further biomarker research and rational development of therapeutics.